Educational Technology in the Teacher Training Process (Docentes 2.0 Journal, 2021)
In this essay, a tour was made of traditional teaching materials and new technologies that have been implemented in teacher training. It was conducted under the premise that education should be designed to cultivate and foster new skills. At present, reference is made to digital literacy. These competencies, necessary in this age, must be improved, redesigned, and rethought from a new perspective. The enormous technological changes that the modern world is experiencing are also transforming social relations. In this context, information is the new engine of progress. Without quality education for all, a knowledge society is impossible. Therefore, faced with emerging skills and new cultures, teachers must take on the challenge of promoting universal access to technologies and the skills necessary to guarantee their use. This line sought to highlight the importance of training in teacher training on new technologies and their implementation in the educational process to improve and promote student learning.
Keywords: Education; ICT; Teacher training